hubungan kualitas pelayanan dengan kepuasan pasien - Iwan Shalahuddin; Theresia Eriyani; Riyanti Riyanti (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Cases of poor nutritional status in toddlers can be found in families that are materially classified as rich, this is due to clean and healthy living behavior that is not in accordance with health standards. In Girimukti Village, Cibatu Health Center, Garut Regency, the majority condition of the education is in low level and only 1591 (32%) of 5569 patriarch had passed Junior High School, and has income in low level, between 300 - 500 thousand (IDR) per month.Purpose: Knowing The effect of family mentoring program (FMP) on improvement of nutritional statusMethods: The type of this study was quasi experimental with pretest, posttest and control design with pretest-posttest quasi experimental design. The study sample was carried out using stratified random sampling with a population of malnourished mothers and under-fives for the Girimukti village area, the working area of Cibatu Community Health Center was 61 people.Results: Statistical test results with a confidence level of 95% showed that there were changes in parents' knowledge about nutrition. The average change in calorie intake consumed by toddlers in the treatment group reached 6.92% of the original calorie intake and the average change in calorie intake consumed in the control group reached 2.10% of the original calorie intake. The results of statistical tests show that there are significant differences in the average changes in calorie intake consumed by toddlers between the treatment group and the control group (p <0.05).Conclusion: From the results of the study it can be concluded that the knowledge and attitudes of mothers of children under five who received family nursing care by students were better than mothers who did not receive family nursing care.